LEFLUNOMIDE IN RHEUMATOID ARTHRITIS: URGENT MATTERS OF PRACTICAL USE - Yuri Aleksandrovich Olyunin (Современная ревматология, 2009)
The period of clinical application of leflunomide (LF) has indicated that by and large the results of its use in the routine practice are comparable with those obtained during clinical trials. The drug provides a considerable improvement in about 50-55% of patients with rheumatoid arthritis (RA) and permits a long monitoring of the disease activity. The rate of adverse reactions (AR) in the use of LF is lower than that in the administration of essential anti-inflammatory drugs (EAID). In most cases, ARs offer no serious threat to a patient and require no drug discontinuation. The duration of LF therapy is largely determined by the severity of the disease in a specific patient and by the qualification of a physician. The application of the standard LF treatment regiment takes about 6 observational months to provide a valid evaluation of the effect of the drug. If its saturated dose is not given, this interval may be much longer. The use of LF in combination with methotrexate (MT) in the patients who have benefited from MT yields better results than continued MT monotherapy and causes no significant increase in the number of AR. In the routine practice, LF has also shown good results when used in combination with biologicals. The currently gained clinical experience with LF enables the latter to be recommended for wide application in any types of RA both as basic monotherapy and in combination with other EAIDs and biologicals.